Fresno County Bar Association Law Day Luncheon: Judge Robert Coyle Speaker - Watkins, Howard::::::::: (1986)
Supervisor Deran Koligian at lectern; Thomas Richey, Catherine Golden-Taylor, Judge Robert Coyle and Faye Coyle